PENERAPAN METODE PEMBELAJARAN TILAWATI DALAM MEMBACA AL-QUR'AN DI TPA AL-HUDA JAMBAN, WONOGIRI - Fadela, Rachma; Nashir, M. Ja’far (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This journal describes the implementation of the tilawati method at TPA Al-Huda Jamban. In addition, it also answers several research questions as as follows: (1) how is the implementation of the tilawati method at TPA Al-Huda and (2) what are the supporting and inhibiting factors in implementing tilawati method at tilawati method at TPA Al-Huda. By using a qualitative and descriptive approach this study obtained research data from interviews, observations, and documentation. The results of this study indicate that (1) the implementation of the tilawati method at TPA AL-Huda. The results of this study indicate that (2) the implementation of the tilawati method at TPA Al-Huda is quite good. There are classical and individual approaches used in implementing the tilawati method. Both of these approaches are used continuously in the supporting factors in implementing the tilawati method are: the classical and individual approaches used in implementing the tilawati method are: (a) the tilawati method has been included in the curriculum (b) there is good support from teachers (both internal and external) and the foundation, (c) competent teachers always provide good support. While the inhibiting factors for the implementation of the tilawati method are: (a)Tilawati method are: (a) the tilawati method is: (b) the lack of competent teachers who can competent, (c) the laziness of students who do not want to read back at home, (d) lack of monitoring from parents, (e) the lack of support from parents.